Sortilin-related receptor is a druggable therapeutic target in breast cancer - Al-Akhrass Hussein; Pietilä Mika; Lilja Johanna; Vesilahti Ella-Maria; Anttila Johanna M.; Haikala Heidi M.; Munne Pauliina M.; Klefström Juha; Peuhu Emilia; Ivaska Johanna (WILEY, 2022)
In breast cancer, the currently approved anti-receptor tyrosine-protein kinase erbB-2 (HER2) therapies do not fully meet the expected clinical goals due to therapy resistance. Identifying alternative HER2-related therapeutic targets could offer a means to overcome these resistance mechanisms. We have previously demonstrated that an endosomal sorting protein, sortilin-related receptor (SorLA), regulates the traffic and signaling of HER2 and HER3, thus promoting resistance to HER2-targeted therapy in breast cancer. This study aims to assess the feasibility of targeting SorLA using a monoclonal antibody. Our results demonstrate that anti-SorLA antibody (SorLA ab) alters the resistance of breast cancer cells to HER2 monoclonal antibody trastuzumab in vitro and in ovo. We found that SorLA ab and trastuzumab combination therapy also inhibits tumor cell proliferation and tumor cell density in a mouse xenograft model of HER2-positive breast cancer. In addition, SorLA ab inhibits the proliferation of breast cancer patient-derived explant three-dimensional cultures. These results provide, for the first time, proof of principle that SorLA is a druggable target in breast cancer.